MASTERPLAN DRAINASE KOTA SINTANG - Saputro, Bayu; Ghani, Umar A.; Yulianto, Eko (Jurnal Mahasiswa Teknik Sipil Universitas Tanjungpura, 2018)
Drainage infrastructure is a system consisting of many components, then drainage infrastructure planning should consider the interconnection between components, along with their impacts. Planning of drainage infrastructure is a process with high complexity, multi discipline, multi sector and multi user. The best planning is based on a global approach but still concentrating specifically (sectorally) on the key issues to be solved. Sintang City often experienced floods that resulted in disruption of community activities and the destruction of infrastructure such as roads, bridges and settlements. Sintang City bypassed by the confluence of two major rivers namely the Kapuas River and the Melawi River that divides the city into three parts. Sintang City also there are many small rivers which is the part of Kapuas and Melawi River. This will result in a decrease in the conductivity of the flow so that it is troubled to flooding. The purpose and objectives to be achieved in this research is as to study the topography and hydrotopography characteristics of Sintang City in relation to the drainage of the region, to examine the characteristics of the Sintang flood which includes the source of flood water, the flood type, the puddle area, etc., to examine the macro drainage system which is right for Sintang City. Research methodology used by writer in this case is with ex facto method which is comparative and associative. Data analysis also uses descriptive analytical method which is adjusted with the research flow diagram. Secondary and primary data inventory as well as pre-arranged drainage masterplan planning through existing regulations in order to become a reference in conducting studies and analysis, planning urban drainage network system including determining its priority scale and stages of handling. Data analysis is also done with some software as a tools in modeling the frequency distribution of rainfall, drainage flow modeling, and spatial approach to the condition in a city area, especially the global contour in this case is Sintang City. The result of the research with the data analysis showed that from the hydrology analysis of the maximum daily rainfall frequency distribution used the value is relatively the same for one region, where the value of the maximum flood discharge that occurs rapidly due because rainfall intensity factor that occurs quite swift with a short duration of this can be seen in each hydrograph flooding each river. Furthermore, there are floods of shipment that occur from upstream in 2 major rivers, namely Kapuas River and Melawi River which high water level (HWL) becomes a reference in determining river border and become boundary conditions measurement in hydrometry analysis and also related to river flow modeling, viewed through a spatial approach related to the global contours that the Sintang City region especially in the River/Drainage Primary there are basins with elevation of existing hydrotopography as well as zonation of loading from the existing catchment area has a variety of different land use designs so that the surface runoff becomes large and that affect the existing flow coefficient. Some of these factors are the cause of the problem of floods/puddles that periods often occur in the Sintang City area. Therefore, it is necessary to determine the priority scale, the matrix of problems and the appropriate treatment alternatives in the context of flood control seen from the method and time of handling especially on the primary rivers according to the typology of Sintang City area so as to produce technical recommendations related to flood prevention. Keywords: masterplan, system, drainage, infrastructure, city, river